Research on the oxygen reduction reaction (ORR) mechanism of g‐C3N4 doped by Ag based on first‐principles calculations - Zhang, Yuanyuan; Huang, Naibao; Zhou, Feng; He, Qiuchen; Zhan, Su (Journal of the Chinese Chemical Society (Taipei), 2018)
Developing non‐platinum composite catalysts has become a hot research topic for the oxygen reduction reaction (ORR). In this study, Ag/g‐C3N4 (the mass ratio of Ag and g‐C3N4 = 3%) catalysts were prepared through a photoreduction method. The catalytic performance of g‐C3N4 was greatly enhanced after Ag doping. The current density of Ag/g‐C3N4 was −21 μA/mm2, which is 3 times that of pure g‐C3N4. The mechanism of ORR activity enhancement is discussed based on first‐principles calculation. Ag, as the active site, can reduce the reaction barrier and enhance ORR activity. Combining experimental and computational results forms the subject of this study. Ag‐doped g‐C3N4 (Ag/g‐C3N4) is prepared by a photoreduction method. Based on the calculation of cohesive energy and cluster energy, the Ag can be stably loaded on the g‐C3N4 surface. Activity test results indicate that the current density of is 3 times that of pure g‐C3N4 and the catalytic performance of g‐C3N4 is greatly enhanced after Ag doping